Evaluating an autonomous electric robot for real farming applications - Gabriele Sara; Giuseppe Todde; Daniele Pinna; Maria Caria (Smart Agricultural Technology)
Mobile robotic technologies are emerging in agriculture in recent years, driven by labor shortages, the need of precision farm management, and the improvement of farmers' quality of life. Mobile robotic technologies, both aerial and ground, have been considered as one of the most important and promising solutions to address agricultural challenges. Nevertheless, the implementation rate in farms is still low. The aim of this study was to evaluate the performance of a mobile agricultural ground robot to assess its possible implementation in the farm environment. The mobility performances as well as the energy consumption of the mobile robot were evaluated considering different interaction systems (teleoperated, autonomous driving) and application areas (weeding, tilling). The results show that the forward speed of the tested mobile robot is affected by the towed load, up to 230 kg, and that the robot could be driven continuously for 2 h in the field without decreasing its performances at a maximum speed between 0.71–0.77 m s-1. The autonomy of the tested robot is limited, but this is mainly due to the battery technology used. The mobile robot effectively tow implements for weeding and tilling operations managing grass with a single pass (40 % weed removal) and improving soil bulk density. The average energy consumption across the different settings was about 1.43 kWh for each hour of use. Moreover, although the RTK-GNSS autonomous navigation used was a low-cost system, the results showed a good accuracy, which allowed the mobile robot to navigate autonomously in the 2 m inter-row of the vineyard. Finally, the working capacity of the mobile robots, considering the implements used, is on average 0.29 ha h-1. This study provides further evidence for the possible use of ground mobile robot in agriculture to carry out autonomous or semi-autonomous operations.